Updates of 2d calculations of brake level transmissions for increasing the resource of the wagon pads (Transport systems and technologies, 2020)
The complex of theoretical scientific researches is conducted in the work, which proves that the typical design of brake lever transmission of three-element carts does not provide normative wear of the pads, therefore it requires correct researches, and its structure - modernization and revision of functional purpose of some elements. On the basis of 2D circuit models, analytical calculations were performed with a comparative analysis of their different design solutions — elements of the brake levers of three-element trucks of freight wagons. As a result, practical changes were made to the knot of the vertical linkage with the triangel spacer, and a reasonable distance between the hinge joint and the triangel beam.Comprehensive comparative calculations of the power factors acting in the elements of the lever gears during braking of the trolley for different cases of alternating vertical forces of inertia, at the collision of the carts on the inequality of the rail track of the type "rail joint", were made.The results of the theoretical calculations, which were obtained were confirmed by the experimental operation of freight wagons with innovative three-element trolley braking systems, which makes it possible to choose a rational calculation 2D circuit model of the brake lever transmission during design.Thanks to the proposed methodology and its application in railway and railcar enterprises, it is possible to significantly increase their competitiveness, reduce the intensity of brake pad wear and increase their life during the operation of freight wagons.
Keywords: wagon, trolley, brake lever gear, brake pad, wear, triangles